Iron regulatory proteins secure mitochondrial iron sufficiency and function - Galy, Bruno; Ferring-Appel, Dunja; Sauer, Sven; Kaden, Sylvia; Lyoumi, Saïd; Puy, Herve; Kölker, Stefan; Gröne, Hermann-Josef; Hentze, Matthias W. (Cell metabolism, 2010)
Mitochondria supply cells with ATP, heme, and iron sulfur clusters (ISC), and mitochondrial energy metabolism involves both heme- and ISC-dependent enzymes. Here, we show that mitochondrial iron supply and function require iron regulatory proteins (IRP), cytosolic RNA-binding proteins that control mRNA translation and stability. Mice lacking both IRP1 and IRP2 in their hepatocytes suffer from mitochondrial iron deficiency and dysfunction associated with alterations of the ISC and heme biosynthetic pathways, leading to liver failure and death. These results uncover a major role of the IRPs in cell biology: to ensure adequate iron supply to the mitochondrion for proper function of this critical organelle.
Gesehen am 25.07.2023